2018
DOI: 10.1051/jnwpu/20183661037
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Characteristic Analysis of Ship's Air Flow Field

Abstract: The air flow field of ship was simulated by using computational fluid dynamics technology to analyze its prime characteristics with reasonable accuracy. The different results of Reynolds-Averaged Navier-Stokes (RANS) method and Detached Eddy Simulation (DES) were compared, and the calculation traits of these methods were discussed. The results show that the air flow field of ship is unsteady. The accuracy of RANS simulation is insufficient for capturing this unsteady phenomenon. However, DES can catch this wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Polsky conducted a series of calculations on the models of amphibious assault ship (LHA) and nuclearpowered aircraft carrier (CVN), and studied the Reynolds number independence and Mach number independence, indicating that the grid mass is crucial to the prediction of flow in the separation area [1][2][3].There are also some literatures on the accurate simulation of ship's seakeeping and free surface [4][5].Crozon used HMB2 code to calculate the mutual interference between rotors and Canadian patrol ships, compared the difference between the excitation disk model and the real blade, and showed that the excitation disk model based on steady calculation can better predict the main characteristics of the flow field [6].Li Xu used nested grid technology to simulate the landing of UAV in the dangling state of aircraft carrier, and studied the influence of carrier wake flow field on carrier-borne aircraft landing [7].Bao Feng took the shrinkage model of Liaoning as the research object, studied its wake structure in a tank, and used dyeing liquid flow display technology and particle imaging velocity measurement technology to display and measure the change of aircraft carrier's wake structure with course Angle, velocity and key position [8].In the literature, Ben Liangliang took Nimitz-class aircraft carrier as the research object, established simplified three-dimensional digital model, and carried out flow field simulation of carrier-borne aircraft entry trajectory [9]; Taking the aircraft carrier "Kuzzonev" as the research object, Tudian discussed the influence of mesh type, mesh density and turbulence model on the flow field values through numerical simulation and comparison, and analyzed the flow field changes at key locations and their influence on the aerodynamic characteristics of carrier-borne aircraft [10].Guo Jiahao simulated the air flow field of aircraft carrier based on DES method, which accurately captured the generation and shedding of vortices in the flow field. He found that complex vortex systems interfered with each other at the blunt edges of aircraft carrier, such as the island and deck, which resulted in strong periodic velocity fluctuations on the carrier-borne aircraft entry trajectory [11].Su Shipeng with American "cock wake" model for reference, using experimental method, measurement of carrier air wake flow field model of the glide path, analysis its law characteristic and the influence of ship island to glide path [12].In view of the influence of carrier wake on the aerodynamic characteristics of carrier-borne aircraft during landing, Li Xu adopted nested grid method to conduct numerical simulation of the landing process of UAV under different wind directions [13].Based on computational fluid dynamics technology, Kou Yajun numerically simulated the flow field of aircraft carrier roll and pitch deck, and obtained the influence of different wind directions on air flow field characteristics of flight deck [14].Based on the flight dynamics theory and considering the characteristics of aircraft carrier...…”
Section: Research Statusmentioning
confidence: 99%
“…Polsky conducted a series of calculations on the models of amphibious assault ship (LHA) and nuclearpowered aircraft carrier (CVN), and studied the Reynolds number independence and Mach number independence, indicating that the grid mass is crucial to the prediction of flow in the separation area [1][2][3].There are also some literatures on the accurate simulation of ship's seakeeping and free surface [4][5].Crozon used HMB2 code to calculate the mutual interference between rotors and Canadian patrol ships, compared the difference between the excitation disk model and the real blade, and showed that the excitation disk model based on steady calculation can better predict the main characteristics of the flow field [6].Li Xu used nested grid technology to simulate the landing of UAV in the dangling state of aircraft carrier, and studied the influence of carrier wake flow field on carrier-borne aircraft landing [7].Bao Feng took the shrinkage model of Liaoning as the research object, studied its wake structure in a tank, and used dyeing liquid flow display technology and particle imaging velocity measurement technology to display and measure the change of aircraft carrier's wake structure with course Angle, velocity and key position [8].In the literature, Ben Liangliang took Nimitz-class aircraft carrier as the research object, established simplified three-dimensional digital model, and carried out flow field simulation of carrier-borne aircraft entry trajectory [9]; Taking the aircraft carrier "Kuzzonev" as the research object, Tudian discussed the influence of mesh type, mesh density and turbulence model on the flow field values through numerical simulation and comparison, and analyzed the flow field changes at key locations and their influence on the aerodynamic characteristics of carrier-borne aircraft [10].Guo Jiahao simulated the air flow field of aircraft carrier based on DES method, which accurately captured the generation and shedding of vortices in the flow field. He found that complex vortex systems interfered with each other at the blunt edges of aircraft carrier, such as the island and deck, which resulted in strong periodic velocity fluctuations on the carrier-borne aircraft entry trajectory [11].Su Shipeng with American "cock wake" model for reference, using experimental method, measurement of carrier air wake flow field model of the glide path, analysis its law characteristic and the influence of ship island to glide path [12].In view of the influence of carrier wake on the aerodynamic characteristics of carrier-borne aircraft during landing, Li Xu adopted nested grid method to conduct numerical simulation of the landing process of UAV under different wind directions [13].Based on computational fluid dynamics technology, Kou Yajun numerically simulated the flow field of aircraft carrier roll and pitch deck, and obtained the influence of different wind directions on air flow field characteristics of flight deck [14].Based on the flight dynamics theory and considering the characteristics of aircraft carrier...…”
Section: Research Statusmentioning
confidence: 99%
“…Adiabatic temperature rise refers to the increase of material temperature caused by the heat generated by plastic deformation of materials, which cannot be rapidly spread to the outside world. The adiabatic temperature rise in the impact process is generally calculated by the following formula 21 where is the density of frozen soil, is the specific heat of frozen soil, and is the work-thermal conversion factor of the material.…”
Section: The Evolution Of the Volume Fraction Of Ice Particlesmentioning
confidence: 99%
“…A large number of studies 20 , 21 have shown that under impact loading, materials are in an adiabatic state and their internal temperature rises sharply. For frozen soil, the adiabatic temperature rise will change the volume fraction of ice and lead to change in the mechanical properties of the frozen soil.…”
Section: Introductionmentioning
confidence: 99%